A Business Architecture Framework for Streamlining Post-Production Workflows in the Film Industry - Wilson; Alfa Ryano Yohannis; Erick Dazki (Politeknik Pertanian Negeri Samarinda, 2025)
The post-production phase of filmmaking is a complex sequence of activities that directly impacts artistic quality, cost-efficiency, and time-to-market. Despite advancements in editing suites and asset repositories, many studios face fragmented systems, manual bottlenecks, and version-control conflicts. This paper presents a comprehensive Business Architecture framework, modeled using ArchiMate and aligned with the TOGAF Architecture Development Method (ADM), to transform post-production into an integrated, transparent ecosystem. We systematically map the current (